A sediment flow‐through system to study the impact of shifting fluid and methane flow regimes on the efficiency of the benthic methane filter. (28th January 2014) - Steeb, Philip; Linke, Peter; Treude, Tina
<x xml:space="preserve">Abstract</x> The efficiency of the "benthic microbial methane filter" at marine cold seeps is controlled by diffusive sulfate supply from the overlying seawater and advective methane flux from deep reservoirs. High fluid fluxes reduce the penetration depth of sulfate and limit the filter to a very narrow zone close to the sediment‐water interface. Here, we introduce a new sediment‐flow‐through (SLOT) system, to mimic the balance between fluid/methane flow and sulfate supply in natural sediments. SLOT enables anaerobic incubations of intact sediment cores under natural flow regimes. In addition to traditional in‐ and outflow sampling, geochemical parameters can be monitored along the sediment core using microsensors and rhizons. In a first test run, two cores with gassy sediments from the Eckernförde Bay (Baltic Sea) were incubated and monitored for 310 days under low (11.2 cm y−1) and high fluid flow (112.1 cm y−1) conditions. Rates of anaerobic oxidation of methane (AOM) were one order of magnitude higher (3.07 mmol m−2 d−1) in the high flow compared to the low flow regime (0.29 mmol m−2 d−1), whereas methane efflux was twice as high (0.063 and 0.033 mmol m−2 d−1, respectively). Sediment profiles of sulfide, sulfate, total alkalinity, pH, redox, and other parameters offered important information on the nature and dynamics of the biogeochemical reactions in the sediment cores including methanotrophy, sulfate reduction, carbonate precipitation, and sulfide oxidation. The SLOT system proofed to be an effective device to study the temporal evolution of biogeochemical parameters in intact sediments subjected to advective fluid transport.